Translation in Intersystemic Interaction: A Case Study of Eighteenth-Century Russia - Tyulenev, Sergey (TTR)

(untitled) (Association canadienne de traductologie, 2010)
The article considers the applicability of Niklas Luhmann’s social systems theory to the study of translation. The focus of this paper is the intersystemic aspect of translation’s social involvements. Translation is considered as a social subsystem acting as a boundary phenomenon (opening/closing the system) and as a mechanism of the system/environment throughput. The theory of social-systemic functioning of translation is exemplified by a case study of the translation history of eighteenth-century Russia.